Google Assistant-Enabled Smart Lock System Using NodeMCU ESP8266 for IoT - Arditya Dwifians (Komunitas Dosen Indonesia, 2024)
Security is an important aspect that needs to be considered in a smart lock system. Conventional key tools currently have low security levels and are vulnerable to attacks. Therefore, this research aims to design a smart lock security system that utilizes Google Assistant features from Google and the NodeMCU ESP8266 module based on the Internet of Things (IoT). By using Google Assistant, users can control this smart lock with voice commands. The NodeMCU ESP8266 is used as the main controller in this system, responsible for receiving commands from Google Assistant and controlling the smart lock mechanism. A prototype implementation was conducted to test the performance of this smart lock security system. In the testing phase, the system's performance was measured based on voice command responsiveness, response speed, and the security it provides. The test results show that this smart lock security system offers a higher level of security compared to conventional key tools, with a security satisfaction rate of up to 90% among the 10 respondents related to the use of this device. With this research, it is expected to enhance community security by introducing a safer and more reliable smart lock tool based on virtual assistant. This security system, utilizing Google Assistant features and the NodeMCU ESP8266, can provide ease and convenience for users while maintaining optimal security.